2006
DOI: 10.1158/1535-7163.mct-05-0370
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets for apigenin-induced cell cycle arrest and apoptosis in prostate cancer cell xenograft

Abstract: Apigenin (4V ,5,7-trihydroxyflavone) is a promising chemopreventive agent abundantly present in fruits and vegetables that has been shown to promote cell cycle arrest and apoptosis in various malignant cell lines. To determine whether pharmacologic intervention with apigenin has a direct growth inhibitory effect on human prostate tumors implanted in athymic nude mice, we examined cell cycle regulatory molecules as precise molecular targets of apigenin action. Apigenin feeding by gavage to these mice at doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 45 publications
7
78
1
1
Order By: Relevance
“…The second and third groups of animals received 20 and 50 μg/mouse/day doses of apigenin in vehicle, respectively, for 10 weeks. These doses are comparable to the daily consumption of flavonoid in humans as reported in previously published studies [33,34]. Apigenin feeding was started 2 weeks before cell inoculation and was continued for 10 weeks.…”
Section: Experimental Design For Tumor Xenograft Studiessupporting
confidence: 69%
See 2 more Smart Citations
“…The second and third groups of animals received 20 and 50 μg/mouse/day doses of apigenin in vehicle, respectively, for 10 weeks. These doses are comparable to the daily consumption of flavonoid in humans as reported in previously published studies [33,34]. Apigenin feeding was started 2 weeks before cell inoculation and was continued for 10 weeks.…”
Section: Experimental Design For Tumor Xenograft Studiessupporting
confidence: 69%
“…This induction of apoptosis is accompanied by increases in ROS production, p53 phosphorylation, and p21/WAF-1 induction; alterations in MDM2/p14 ARF ; a decrease in NF-κB/p65 transcriptional activity leading to loss of mitochondrial membrane potential; and caspase activation. Although our study and prior studies have shown that apigenin-induced p53-dependent apoptosis occurs in prostate cancer and other malignancies, the pathways whereby p53 leads to execution of the apoptosis program are not well characterized.There is accumulating evidence that apigenin can suppress the growth of malignant prostate cells as well as tumor xenografts in vivo by causing cell cycle arrest and apoptosis [31][32][33][34]36]. In this study we have demonstrated that the p53-associated pathway is required for apigenin-mediated apoptosis, as evidenced by the p53 antisense oligonucleotide experiment.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, one of the possible molecular targets in cancer cells is the activation of CDK inhibitors. Indeed, our observation that PC treatment significantly increased expression of CDK inhibitor CDKN1A-p21, is in agreement with recent studies demonstrating that some natural compounds (apigenin, silibinin, white cocoa tea extract) inhibited growth of PC-3 tumor xenografts and increased protein levels of p21 in these tumors (27)(28)(29).…”
Section: Effect Of Pc On the Gene Expression In Tumorssupporting
confidence: 93%
“…The study of CP-31398 (17) referred to in the introduction provides convincing support for the notion that increasing expression and activation of wild-type p53 reduces intestinal adenoma development in the Apc Min mouse, probably through the suppression of adenoma cell proliferation and induction of apoptosis. The p53-modulating ability of flavonoids in cells in vitro has been described before (10,11,(43)(44)(45)(46), although flavonoid-mediated upregulation of p53 in intact animals has to our knowledge been shown previously only for the flavone apigenin (4′,5,7-trihydroxyflavone) in mice bearing the 22Rv1 prostate tumor xenograft (45). TMFol at 10 μmol/L doubled p53 protein expression in HCT116 cells in vitro, and fisetin has been reported to have a similar effect (44).…”
Section: Ability In the Apcmentioning
confidence: 96%